2013
DOI: 10.1002/da.22113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine Withdrawal on Panic-Like Response to Breath Holding: A Placebo-Controlled, Double-Blind, Crossover Patch Study

Abstract: The findings for heart rate and BP are consistent with the stimulant properties of nicotine. The reduced capacity to maintain apnea under placebo might be due to carbon dioxide (CO2 ) hypersensitivity during periods of nicotine abstinence. The negative findings regarding fear reactivity might be due to BH being a relatively weak anxiogen. Future researchers are encouraged to employ CO2 -inhalation procedures to study the relationship between nicotine withdrawal and panic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Theory suggests that nicotine deprivation in daily smokers may heighten sensitivity to bodily sensations and/or arterial CO 2 (Breslau & Klein, ). The present study, however, joins other experimental studies that found no evidence that nicotine deprivation promotes subjective fear reactivity (Abrams et al., ; Cosci et al., ; Cosci et al., ; Vujanovic et al., ) or found evidence that withdrawal lowers subjective fear reactivity (Leyro & Zvolensky, ; Vujanovic & Zvolensky, ). As such, the findings do not support the idea that smoking cessation programs will be more effective if accompanied by treatment for panic attacks.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Theory suggests that nicotine deprivation in daily smokers may heighten sensitivity to bodily sensations and/or arterial CO 2 (Breslau & Klein, ). The present study, however, joins other experimental studies that found no evidence that nicotine deprivation promotes subjective fear reactivity (Abrams et al., ; Cosci et al., ; Cosci et al., ; Vujanovic et al., ) or found evidence that withdrawal lowers subjective fear reactivity (Leyro & Zvolensky, ; Vujanovic & Zvolensky, ). As such, the findings do not support the idea that smoking cessation programs will be more effective if accompanied by treatment for panic attacks.…”
Section: Discussionsupporting
confidence: 78%
“…To increase internal validity, individuals were excluded if they had prior experience with a CO 2 challenge or used psychotropic medication (such as antidepressants, anxiolytics, mood stabilizers, or beta blockers) on a daily basis. Also, to increase power and aid interpretation of the data, permit conclusions regarding the etiology of co‐occurring smoking and PD, and maintain precedence with related studies (e.g., Abrams et al., ; Cosci et al., ; Cosci, Aldi, & Nardi, ; Leyro & Zvolensky, ), we excluded individuals with a lifetime history of PD. We permitted individuals who used psychotropic medication (such as anxiolytics) on an “as needed” basis to participate if they volunteered to abstain for the 3 days prior to the study sessions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are mainly negative results since it is not possible to disentangle whether the difference for respiratory rate was a true response to the breath holding test or a consequence of a different pre-test end tidal pCO 2 , which was not measured. These results can, once again, be explained as a lack of influence of nicotine abstinence on the response to a biological challenge (Cosci et al, 2013, accepted for publication) but may also support a poor validity of the breath holding test as a task to assess distress tolerance (Sütterlin et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…We also found an increased heart rate and systolic blood pressure from baseline to pre-test under nicotine; and lower tobacco withdrawal symptoms under nicotine if compared to placebo. These latter findings do not deserve discussion since the increased heart rate and blood pressure are widely explained by the stimulant properties of nicotine (Cosci et al, 2013, accepted for publication) while the different level of tobacco withdrawal symptoms is a consequence of the manipulation of the dependent variable.…”
Section: Discussionmentioning
confidence: 99%